Construct validity and parent–child agreement of the six new or modified disorders included in the Spanish version of the Kiddie Schedule for Affective Disorders and Schizophrenia present and Lifetime Version DSM-5 (K-SADS-PL-5). (June 2018) - de la Peña, Francisco R.; Rosetti, Marcos F.; Rodríguez-Delgado, Andrés; Villavicencio, Lino R.; Palacio, Juan D.; Montiel, Cecilia; Mayer, Pablo A.; Félix, Fernando J.; Larraguibel, Marcela; Viola, Laura; Ortiz, Silvia; Fernández, Sofía; et al.
Abstract: Changes to the Diagnostic and Statistical Manual of Mental Disorders fifth edition (DSM-5) incorporate the inclusion or modification of six disorders: Autism Spectrum Disorder, Social Anxiety Disorder, Intermittent Explosive Disorder, Disruptive Mood Dysregulation Disorder, Avoidant/Restrictive Food Intake Disorder and Binge Eating Disorder. The objectives of this study were to assess the construct validity and parent-child agreement of these six disorders in the Spanish language Schedule for Affective Disorders and Schizophrenia for School Age Children Present and Lifetime Version (K-SADS-PL-5) in a clinical population of children and adolescents from Latin America. The Spanish version of the K-SADS-PL was modified to integrate changes made to the DSM-5. Clinicians received training in the K-SADS-PL-5 and 90% agreement between raters was obtained. A total of 80 patients were recruited in four different countries in Latin America. All items from each of the six disorders were included in a factor analysis. Parent-child agreement was calculated for every item of the six disorders, including the effect of sex and age. The factor analysis revealed 6 factors separately grouping the items defining each of the new or modified disorders, with Eigenvalues greater than 2. Very good parent-child agreements ( r >0.8) were found for the large majority of the items (93%), even when considering the sex or age of the patient. This independent grouping of disorders suggests that the manner in which the disorders were included into the K-SADS-PL-5 reflects robustly the DSM-5 constructs and displayed a significant inter-informant reliability. These findings support the use of K-SADS-PL-5 as a clinical and research tool to evaluate these new or modified diagnoses.